Ekstraksi dan Formulasi Suspensi Oral Teripang Holothuria scabra sebagai Sumber Antioksidan - Ardi Ardiansyah (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
Extraction and Oral Suspension Formulation of Sea Cucumber Holothuria scabra as Source of Antioxidants. Sea cucumbers have long been utilized in the food and medicine for Asia and Middle East communities. Indonesia is one of the main suppliers in the trade of sea cucumbers in Asia. Sea cucumber utilization in Indonesia is generally done only in the form of raw materials. Holothuria scabra is one of the sea cucumber that can be explored as a potential source of antioxidants. This study aims to determine the antioxidant activity of sea cucumber H.scabra in extract and suspension. Sea cucumber was extracted with methanol 96% and ethanol 96%, then both antioxidant activity was tested. Extract with higher antioxidant activity were made into oral suspension preparation for further evaluation of the stability (organoleptic, pH, microorganisms) and antioxidant testing. The results showed that ethanol extracts had higher antioxidant activity of methanol extract, but still lower than ascorbic acid. Based on the calculation, IC50 of methanol extract was 316.85 ppm and ethanol extract was 130.54 ppm, while ascorbic acid showed IC50 34.06 ppm. The most stable formula (F1a) shows that there is still an antioxidant activity that is equal to 42.11 %.